Erosive Wear Characteristics of Multi-Fiber Reinforced Polyester under Different Operating Conditions - Nuruzzaman, D. M.; Debnath, U. K.; Chowdhury, M. A. (IOP Publishing Ltd., UK, 2016)
Composite materials are used in a wide range of applications. The erosion properties of combination of glass, jute and carbon fiber-reinforced polyester were analyzed in this study. Randomly-shaped silica (SiO2) particles of various sizes (300–355μm, 355-500μm, and 500-600μm) were selected as the erosive element. Impingement angles between 15-90°, impingement velocities between 30-50 m/sec, and stand-off distances of 15-25 mm at ambient temperature were selected. During experiment, the maximum erosion of the tested composite occurred at 60° impingement angle, indicating a semi-ductile nature of the test material. Erosion increased with impact velocity and decreased with stand-off distance. In a dimensional analysis, erosion efficiency (η) and the relationship between friction and erosion were established. Test results were evaluated using Taguchi‟s concept to minimize the observations needed, and ANOVA was used to identify interactions between tested parameters and to identify the most significant parameters. The S/N ratio indicates that there is only percentage of deviation between the predicted and experimental results. In further, sophisticated analyses and GMDH methods were employed, and surface damage was examined using scanning electron microscopy (SEM) to examine the nature of the wear behaviour.